Issues of attracting domestic investments to the economy - Allayarov, Sukhrob Rustamovich; Rizokulova, Elnora Otabek kizi (Science and Education, 2024)
This article highlights the scientific foundations for the effective use of domestic investment potential in the national economy, provides a methodology for assessing the use of domestic investment, analyzes the efficiency of capital and gives recommendations for the effective use of domestic investment.